Optimization of Bio-Oil Pyrolysis Product from Palm Empty Fruit Bunches over H-Zeolite Catalyst using Response Surface Methodology (RSM) - Zainal Fanani; Addy Rachmat; Hasanudin hasanudin; Muhammad Said (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Bio-oil pyrolysis product considered as a promising resource of hydrocarbon compound that can be used as alternative fuel or other application. Palm empty fruit bunch (PEFB) based bio-oil converted into hydrocarbon trough pyrolysis over sulfate activation natural zeolite. Here, we reported an optimization process of bio-oil pyrolysis specifically on temperature and catalyst dose variables by using response surface methodology (RSM). Prior conversion process, PEFB was analyzed to determine cellulose, hemicellulose and lignin content. Sulfate activation natural zeolite confirmed its acidity by ammonia and pyridine adsorption calculated by gravimetric method. Two independent variables namely temperature and catalyst weight used in optimization process by RSM whereas response variable is conversion percentage. Analysis result on cellulose, hemicellulose and lignin content are 45.39%, 30.36% and 20.5% respectively. Catalyst acidity determination based on ammonia and pyridine adsorption gave 1.002 mmol/g and 0.1994 mmol/g. Optimum condition of hydrocracking achieved at 568 °C and 2.1088 g catalyst weight with the product obtained at 62.21% conversion. The best product density is 1.086 g/mL obtained at hydrocracking temperature 554 °C and 2.0362 g catalyst. Based on GC-MS analysis, it was confirmed that the product comprises more straight-chain hydrocarbon than cyclic one. RSM calculation able to formulate the feasible model equation to predict the conversion percentage. The equation is; percent conversion = 60.059 + 14.268T + 9.783W – 25.649T2 – 18.809W2 + 3.114TW, whereas model equation for response variable on product density; ρ= 1.09103 – 0.12356T – 0.09744W + 0.11489T2 + 0.28888W2 – 0.00740TW